Case Report: Acute cerebral infarction caused by left atrial and right ventricular myxoma received emergency operation - Tang, Chengbin; Gao, Xianglong; Chen, Tao; Shao, Jun; Zhu, Tao; Zheng, Xucai; Ren, Chuanli (Frontiers in Cardiovascular Medicine, 2024)
Cardiac myxoma is a rare etiology of ischemic stroke, especially in young people. We report a case of multiple myxomas in left atrium and right ventricle inducing acute cerebral infarction. No significant abnormalities were detected in the patient's preoperative laboratory examination. Following emergency surgery, the patient's prognosis was satisfactory, providing valuable empirical insight for the surgical management of acute cerebral infarction in individuals diagnosed with cardiac myxoma. Our objective is to heighten awareness regarding the evaluation and treatment of patients with acute cerebral infarction subsequent to early diagnosis of cardiac myxoma.